Online Tools for Electrical and Electronics Education - Serafin, Cestmir (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2021)
The efficiency of the education is variable, which is very difficult to measure, influenced by a variety of input components-students, teachers, school curricula, the school’s internal and external factors. Generally, it is necessary to assess the degree of efficiency of the functioning of the training to carry out a comparison of the rate variables describing the inputs with the same intensity of quantities characterizing the outputs. This article deals with the intermediate results of the research evaluating the scope of the efficiency of the functioning of the educational process in the field of education and training in the context of electrical engineering by on-line education. The research investigated the extent to which online electrical engineering kits have an impact on learning and whether their use has a corresponding impact on learning outcomes. The object of the research was the students and the subject of the research was their knowledge and understanding.